Aramaic magic bowls in the Vorderasiatisches Museum in Berlin: descriptive list and edition of selected texts - Bhayro, Siam (Magical and religious literature of Late Antiquity, 2018)
Introduction -- Text Editions -- VA.2182 -- VA.3854 -- VA.2418 -- VA.2428 -- VA.Bab.2829 + VA.unnumberedD -- VA.2269 -- VA.2510 -- VA.2419 -- VA.2445 + VA.unnumberedC -- VA.2439 + VA.unnumberedA (rim) + VA.unnumberedB (side) -- VA.2435 -- VA.3383 -- VA.Bab.2765 -- VA.Bab.4167i -- VA.Bab.2792 -- VA.Bab.2764 and VA.Bab.2840 -- Catalogue.